2014
DOI: 10.1002/hbm.22623
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of the BOLD signal for EEG-informed fMRI

Abstract: Electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) are important tools in cognitive and clinical neuroscience. Combined EEG–fMRI has been shown to help to characterise brain networks involved in epileptic activity, as well as in different sensory, motor and cognitive functions. A good understanding of the electrophysiological correlates of the blood oxygen level-dependent (BOLD) signal is necessary to interpret fMRI maps, particularly when obtained in combination with EEG. We review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 247 publications
(372 reference statements)
6
88
0
Order By: Relevance
“…That is, decreased alpha activity within a region is thought to signify the active engagement of that region during cognitive processes (Klimesch, ; Klimesch et al, ), and similar proposals have been made regarding beta band modulations (Neuper & Pfurtscheller, ). In congruence with this interpretation, simultaneous EEG‐fMRI research has demonstrated negative associations between alpha/beta activity and fMRI activation during cognitive tasks (Michels et al, ; Murta, Leite, Carmichael, Figueiredo, & Lemieux, ; Scheeringa et al, ). Taken together, the theta activity seen in bilateral visual cortices likely reflects early coding mechanisms, while alpha activity observed in bilateral LOC likely indicate processing of specific features inherent to the target stimuli.…”
Section: Discussionmentioning
confidence: 88%
“…That is, decreased alpha activity within a region is thought to signify the active engagement of that region during cognitive processes (Klimesch, ; Klimesch et al, ), and similar proposals have been made regarding beta band modulations (Neuper & Pfurtscheller, ). In congruence with this interpretation, simultaneous EEG‐fMRI research has demonstrated negative associations between alpha/beta activity and fMRI activation during cognitive tasks (Michels et al, ; Murta, Leite, Carmichael, Figueiredo, & Lemieux, ; Scheeringa et al, ). Taken together, the theta activity seen in bilateral visual cortices likely reflects early coding mechanisms, while alpha activity observed in bilateral LOC likely indicate processing of specific features inherent to the target stimuli.…”
Section: Discussionmentioning
confidence: 88%
“…[16][17][18][19][20][21] Under such conditions, BOLD signal reflects approximate linear changes in local neural activity. [22][23][24][25][26][27] This archetypal relationship between BOLD and neural activity is maintained via functional hyperemia and may be disrupted when there are aberrations in the functional hyperemic response. [12][13][14] MS features damage to specific WMMS (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Blood oxygen level dependent (BOLD) functional magnetic resonance imaging (fMRI) is a non-invasive imaging technique commonly used to localise the neuronal activity underlying sensory, or cognitive functions, sleep, or rest (which may include epileptic activity), commonly captured by electrophysiological techniques (Murta et al, 2015). The fMRI whole-brain mapping capability complements the electroencephalogram (EEG) temporal richness, particularly relevant in epilepsy, providing localising information with potential clinical relevance.…”
Section: Introductionmentioning
confidence: 99%